Strategic airport planning - Caves, Robert E. (Pergamon, 1999)
The role of an airport within the air transport system used to be largely incontestable. The system is now being shaped less by the concept of social service and more by market forces. Progressive liberalisation of air transport, together with trends to privatisation and globalisation are causing the roles of airports to change, for planning to become increasingly decentralised, and for the traffic to become more volatile. Airports are increasingly in competition for markets. Yet the markets are limited, and airport expansion is made difficult by environmental pressures that push towards sustainable transport, and the need to justify investment. The book will examine these pressures in order to identify changes that are required to the airport planning process. The major issues to be discussed are: forecasting in an uncertain world; airport market share; airline network choices; political settings and their consequences; economic justification and viability; environmental impacts and their mitigation; cooperative planning; and physical planning challenges. The issues will be illuminated by case studies of representative airport systems: intercontinental gateways, metropolitan multi airport system, provincial and regional airports and developing country systems. The final section will bring together suggestions for ways in which the industry can move forward to a green and profitable future with an appropriate provision of new capacity.